Mysteries of the ancient Americas - Gardner, Joseph L. (New York The readers Digest Association, Inc., 1991)
Read this book from cover to cover, savor it a chapter at a time, or dip into its profusely illustrated pages at random. You will fing amazing stories, startling facts, enduring puzzles, imaginative solutions wherever you turn. This is history but not as you learned it in school.
Keywords: Country Studies